2014
DOI: 10.1111/dme.12459
|View full text |Cite
|
Sign up to set email alerts
|

Aging is associated with increased HbA1c levels, independently of glucose levels and insulin resistance, and also with decreased HbA1c diagnostic specificity

Abstract: In two large datasets, using different methods to measure HbA(1c), the association of age with higher HbA(1c) levels: was consistent and similar; was both statistically and clinically significant; was unexplained by features of aging; and reduced diagnostic specificity. Age should be taken into consideration when using HbA(1c) for the diagnosis and management of diabetes and prediabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
64
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 29 publications
10
64
3
2
Order By: Relevance
“…Studies have shown that A1C values in the older population may not reflect the same estimated mean glucose as in the younger population. Possible reasons for this discrepancy are the commonly present comorbidities that impact red cell life span (e.g., anemia, uremia, renal dysfunction, blood transfusion, erythropoietin therapy) (45,46). In addition, A1C level does not reflect glucose excursions and variability.…”
Section: Glycemic Goalsmentioning
confidence: 99%
“…Studies have shown that A1C values in the older population may not reflect the same estimated mean glucose as in the younger population. Possible reasons for this discrepancy are the commonly present comorbidities that impact red cell life span (e.g., anemia, uremia, renal dysfunction, blood transfusion, erythropoietin therapy) (45,46). In addition, A1C level does not reflect glucose excursions and variability.…”
Section: Glycemic Goalsmentioning
confidence: 99%
“…Despite the low agreement between HbA1c and FPG, they detected a high agreement among negatives (normo-glycemic FPG and normal HbA1c) [37]. Specifying universal cut-off points for HbA1c may be difficult due to ethnic differences, with higher levels observed among people of African origin [44,45], as well as other influencing factors [46]. However, it has been argued that HbA1c is a valid predictor for diabetes, including undiagnosed cases, but should not be used to identify prediabetes [47].…”
Section: Treated Diabetes N=13mentioning
confidence: 99%
“…A cross-sectional analysis in adults without known diabetes in the Screening for Impaired Glucose Tolerance (SIGT) study 2005 to 2008 (n 5 1573) and the National Health and Nutrition Examination Survey (NHANES) 2005 to 2006 (n 5 1184) showed that HbA1c levels increased 0.87 mmol/mol (0.08%) per 10 years in subjects without diabetes, and 0.76 mmol/mol (0.07%) per 10 years in subjects with normal glucose tolerance (all P<.001). 15 In both datasets, the HbA1c level of an 80-year-old individual with normal glucose tolerance would be 3.82 mmol/mol (0.35%) greater than that of a 30-year-old with normal glucose tolerance; a difference that is clinically significant. Moreover, the specificity of HbA1c-based diagnostic criteria for prediabetes decreased substantially with increasing age.…”
mentioning
confidence: 93%
“…Moreover, the specificity of HbA1c-based diagnostic criteria for prediabetes decreased substantially with increasing age. 15 NHANES II showed a 7-mg/dL increase, per decade of life, in plasma glucose 2 hours after a 75-g oral glucose load. 15 In an analysis of individuals in the Baltimore Longitudinal Study of Aging, age had an independent effect on glucose tolerance, even after adjusting for adiposity, fat distribution, and fitness.…”
mentioning
confidence: 97%